IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK TEMA 6 CITA-CITAKU KELAS IV DI MI DARUL HIKAM KOTA BATU - Dina Oktaviana; Devi Wahyu Ertanti; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is based on how the teacher attempts to implement a  scientific approach in thematic learning in the classroom. Many students are still less active and unfocused, an have not even been able to achieve the specified learnig outcomes. The research was conducted at MI Darul Hikam Kota Batu. The purpose of this study is to describe the planning, implementation, and constraints of thematic learning activities with a scientific approach undertaken by grade IV teachers in MI Darul Hikam Kota Batu. This study usesvavqualitativevapproachvtovthe type of casevstudy research. Data collection procedures used are the method of observation, interviews, and documentation. In this study, teachers make various efforts in applying scientific approaches to thematic learning. The results showed that the teacher designed a thematic learning plan with a scientific approach, the teacher carried out a variety of activities in the thematic learning process by applying 5 M in science even though it was not maximal, as well as teachers still face various obstacles in applying science applied in thematic learning. There are solutions made by teachers and Madrasah so that learning runs well, such as evaluating the way learning is done by teachers.